(untitled) (Research, Society and Development, 2023)
The objective of this article was to analyze the role of nursing in the care of women with gestational diabetes in primary health care. To achieve this goal, a narrative literature review was conducted, consisting of the selection and critical analysis of studies published in electronic databases. The results show that nursing plays a key role in the prevention, early detection, and management of gestational diabetes. Activities performed by nurses include performing tests, nutritional counseling, monitoring glucose levels, and administering insulin when necessary. In addition, nurses play an important role in educating and supporting women with gestational diabetes during pregnancy and after delivery. The conclusion of the study is that nursing plays a crucial role in the care of women with gestational diabetes in primary health care. Involving nurses from the beginning of prenatal care can improve maternal and neonatal outcomes and reduce health care costs associated with gestational diabetes. It is essential that nurses have adequate education and training to carry out these activities effectively and safely.